2017
DOI: 10.1111/jfs.12371
|View full text |Cite
|
Sign up to set email alerts
|

Thermal inactivation of Salmonella spp. in commercial tree nut and peanut butters in finished packaging

Abstract: Peanut and tree nut butters have been implicated in Salmonella outbreaks in recent years. Previous studies investigated efficacy of thermal treatments to reduce Salmonella in multiple peanut butter formulations; however, evidence is lacking to support thermal treatment of tree nut butters. This study evaluated thermal treatments to reduce Salmonella in commercial nut butter formulations in final package. Formulations (n 5 6) were inoculated with a Salmonella cocktail and packaged in glass jars before thermal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…This snack contains valuable nutrients, including vitamin B and E, minerals, essential amino acids, dietary fibers, and functional phytochemicals like sterols and flavonoids (West et al, 2012). Despite the nutritional importance of military rations for armed forces, there are some problems with preserving their quality, and they should be consumed in a short time if not properly processed and stored (Wright, Minarsich, Daeschel, & Waite-Cusic, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This snack contains valuable nutrients, including vitamin B and E, minerals, essential amino acids, dietary fibers, and functional phytochemicals like sterols and flavonoids (West et al, 2012). Despite the nutritional importance of military rations for armed forces, there are some problems with preserving their quality, and they should be consumed in a short time if not properly processed and stored (Wright, Minarsich, Daeschel, & Waite-Cusic, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A study found that some heat-resistant Salmonella strains could survive in peanut butter for the duration of its shelf life, even when exposed to temperatures as high as 194 °F (90 °C) for 50 min [26]. A study assessing in-package thermal inactivation of Salmonella spp., including this outbreak strain, inoculated in Brand A nut butters determined that treatment at >90 °C with a 30 min hold-time achieved a >5 log CFU/g reduction, though there were changes in texture, which the authors noted may make the final product unacceptable [27].…”
Section: Discussionmentioning
confidence: 99%
“…When compared with some other nut butters having similar matrixes and comparable water activities, Salmonella spp. appears to show even greater resistance to thermal inactivation in peanut butter (peanut > almond > hazelnut) [65]. More than 60 min of holding at 90 • C was required to achieve a 5 log CFU/g reduction in Salmonella spp.…”
Section: Nature Of Peanut Buttermentioning
confidence: 98%
“…More than 60 min of holding at 90 • C was required to achieve a 5 log CFU/g reduction in Salmonella spp. in peanut butter whereas just about 30 min sufficed to achieve the same 5 log CFU/g reduction in hazelnut and almonds nuts butter formulations [65]. The differences may emanate from the different chemical compositions of the nut matrixes thereby conferring the Salmonella spp.…”
Section: Nature Of Peanut Buttermentioning
confidence: 99%